The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1242/jcs.178046
|View full text |Cite
|
Sign up to set email alerts
|

Impaired mitochondrial Fe-S cluster biogenesis activates the DNA damage response through different signaling mediators

Abstract: Fe-S cluster biogenesis machinery is required for multiple DNA metabolism processes. In this work, we show that, in Saccharomyces cerevisiae, defects at different stages of the mitochondrial Fe-S cluster assembly machinery (ISC) result in increased spontaneous mutation rate and hyper-recombination, accompanied by an increment in Rad52-associated DNA repair foci and a higher phosphorylated state of γH2A histone, altogether supporting the presence of constitutive DNA lesions. Furthermore, ISC assembly machinery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…As an alternative to DNA damage, DDR could be induced by changes in chromatin structure [51], which have been also implicated in mitochondrial stress control of longevity [30,52]. Furthermore, in yeast, mitochondrial dysfunction leads to DDR activation via defective iron-sulfur cluster (ISC) biogenesis [53,54]. Different DNA repair genes which we found to mediate isp-1 mutants phenotypes (e.g., DNA-glycosylases, helicases, nucleases [55][56][57]) rely on ISC, whose biogenesis is impaired by frataxin depletion [58,59] and could be similarly affected upon suppression of ISP-1, an ISC protein itself.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to DNA damage, DDR could be induced by changes in chromatin structure [51], which have been also implicated in mitochondrial stress control of longevity [30,52]. Furthermore, in yeast, mitochondrial dysfunction leads to DDR activation via defective iron-sulfur cluster (ISC) biogenesis [53,54]. Different DNA repair genes which we found to mediate isp-1 mutants phenotypes (e.g., DNA-glycosylases, helicases, nucleases [55][56][57]) rely on ISC, whose biogenesis is impaired by frataxin depletion [58,59] and could be similarly affected upon suppression of ISP-1, an ISC protein itself.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with those results, a recent study has shown that cells lacking Grx5 glutaredoxin, another member of the core mitochondrial ISC synthesis pathway, promote Sml1 protein degradation through a Dun1-dependent but Mec1/Rad53-independent mechanism (59). However, cells lacking non-core ISC member Iba57, which functions in transferring 4Fe-4S clusters to mitochondrial targets (60,61), or cells in which expression of Npb35, an essential component of cytoplasmic iron-sulfur cluster assembly machinery (62), has been repressed, induce Sml1 protein degradation through a mechanism that requires both Dun1 and Mec1 kinase proteins (59). Given that iron deficiency leads to down-regulation of the ISC synthesis pathway, we propose that various signaling pathways modulate Dun1 kinase function through its FHA domain or Thr-380 residue in response to iron limitation.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…The nuclear DNA damage caused by defects of ISC biosynthesis activates at least two different signalling pathways that converge at Dun1p, a protein kinase that controls the DNA damage response in yeast [61]. The DNA damage checkpoint mediated by the Mec1p–Chk1p– Dun1p signaling transduction pathway was found to be activated by dysfunctions in ISC-targeting factors, which are not required for the biogenesis of ISC but act specifically for transferring ISC to mitochondrial target apoproteins [62]. By contrast, dysfunctions of the core mitochondrial ISC assembly machinery induced a second pathway involving a Mec1p-independent activation of Dun1p.…”
Section: Resultsmentioning
confidence: 99%